INTERACTIVE METHODS OF TEACHING THE TOPIC “POLITICS OF LISTENING IN UZBEKISTAN” IN HISTORY LESSONS (Multidisciplinary Journal of Science and Technology, 2026)
This work focuses on using interactive methods to teach the topic “Koreanization Policy in Uzbekistan” in history lessons. Students study the topic independently, analyze historical events, and better understand them through practical activities. Group work, role-playing, discussions, and analysis of historical situations make lessons interesting and effective.